EFFECTS OF HUMAN ACTIVITIES ON THE AFAKA AFFORESTATION PROJECT, KADUNA NORTH, KADUNA STATE, NIGERIA - Jibril, Mamman Shaba; Ariyo, Mary Oluyemisi; Butu, Ali Williams; Emeribe, Chukwudi Nnaemeka (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
The study aimed to investigate the effects of human activities on the Afaka afforestation project, Kaduna State, Nigeria. Structured interview was used to evaluate the level of community involvement in the modification of the forest project, their perceived environmental effects of landcover loss. Landsat images of 1986, 1999 and Sentinel-2 image of 2017 were applied for detection of changes in land use/land cover over the years (1986-2017). The study found that the land cover structure of the forest reserve has changed significantly. In 1986, area under crop cultivation was 19.24%, built-up areas, 0.08%, disturbed forest, 7.57%, gully, 2.60%, riparian vegetation, 2.78% and undisturbed forest, 61.49%. However, by 2017, there were significant changes as the area under crop cultivation 41.18%, built-up areas 0.17%, disturbed forest, 43.17%, gully 5.6%, riparian vegetation 4.66% and undisturbed forest, 1.66%, implying intensive human impacts on the Kaduna Afforestation project in recent time. This could be traced to the increased level of poverty in the community as 75% of the respondents who cannot afford alternative energy supplies such as kerosene and National grid-based electricity, rely on felling of trees for cooking. On the perceived effects of the afforestation project modification, reduced plantation size was 60.5%, decreased soil fertility 19.5%, reduced non-timber products, 11.1%, sheet erosion 6.1%, while flooding 2.8%. The result of the chi-square test reveals significant changes in the area coverage of the forest cover classification at P<0.05. Thus, it can be concluded that the afforestation project did not meet its objectives. There is need for sustainable programmes and policies towards alleviating poverty among the inhabitants of the study area most of which depend on the forest resources for livelihood. This should be followed up with policies to encourage tree planting initiatives to promote forest restoration and ecological integrity of the study area.